2021
DOI: 10.1183/16000617.0123-2021
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibody-associated interstitial lung disease: a review

Abstract: Over the past three decades, an increasing number of publications have reported the association between interstitial lung disease (ILD) and anti-neutrophil cytoplasmic antibody (ANCA) or ANCA-associated vasculitis (AAV). With this increased awareness, we have reviewed the literature to date and provide an update in this narrative review. The vast majority of cases of ILD have been shown to be in the setting of positive anti-myeloperoxidase antibody and can be present in up to 45% of patients of microscopic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 91 publications
(120 reference statements)
4
35
0
1
Order By: Relevance
“…In previous reports, radiological analysis, especially by high-resolution computed tomography (HRCT), was used for the classification of patterns [27,28] in patients with MPO-ANCA-positive ILD. In patients with MPA, the most frequently occurring pattern was usual interstitial pneumonia (UIP) (50-78%), followed by nonspecific interstitial pneumonia (NSIP) (7-58%) and others (13-31%) [14,[29][30][31][32]. MPO-ANCA-positive ILD without systemic vasculitis (i.e., idiopathic ILD) also showed a similar tendency (UIP: 12.9-53.9%, non-UIP: 13.6-58.1%) [31,32].…”
Section: Radiological Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous reports, radiological analysis, especially by high-resolution computed tomography (HRCT), was used for the classification of patterns [27,28] in patients with MPO-ANCA-positive ILD. In patients with MPA, the most frequently occurring pattern was usual interstitial pneumonia (UIP) (50-78%), followed by nonspecific interstitial pneumonia (NSIP) (7-58%) and others (13-31%) [14,[29][30][31][32]. MPO-ANCA-positive ILD without systemic vasculitis (i.e., idiopathic ILD) also showed a similar tendency (UIP: 12.9-53.9%, non-UIP: 13.6-58.1%) [31,32].…”
Section: Radiological Findingsmentioning
confidence: 99%
“…We reported that an anterior upper lobe honeycomb-like lesion, which represents a concentration of cystic air spaces within the anterior aspect of the upper lobes (Figure 1B), might be found with higher frequency in MPO-ANCA-positive ILD and RA-ILD than in other etiologies associated with ILD [31,42]. Pathologically, MPO-ANCA-positive ILD even with a UIP pattern showed more prominent inflammatory cell infiltration and cellular bronchiolitis, unlike UIP/IPF (Figure 2A-E) [8,14,17,[33][34][35]. In other words, these pathological features correspond well to the presence of a radiological feature such as increased attenuation around areas of honeycombing and traction bronchiectasis [30,31,34].…”
Section: Differences Between Mpo-anca-positive Ild and Uip/ipfmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with MPA, especially those who are ANCA-MPO-positive, may have interstitial lung disease (ILD) [ 4 , 5 ], which is associated with high morbidity and mortality as it is often underdiagnosed and responds poorly to conventional treatments [ 6 ]. Interstitial lung disease associated with AAV does not have specific imaging or bronchoalveolar lavage (BAL) findings.…”
Section: Introductionmentioning
confidence: 99%